Modeling of Globoidal Cam Planetary Mechanism by Simulating Motion Method - Liu Beibei; Cao Jujiang; Zhang Yanhua (Jixie chuandong)
Aiming at the problem of modeling difficult of complex meshing surfaces of globoidal cam planetary mechanism,a method of 3D modeling by using simulated motion method is proposed in order to facilitate the modeling of the mechanism. The kinematics analysis of the mechanism must be carried out in this method and the motion simulation of analog components is carried out according to the motion relationship. The trajectory obtained by using simulation is scanned on the modeled component. Finally,the 3D model of the component is obtained. It is proved that the model is global free of interference and the motion form is simulated correctly.The method is efficient and accurate,the trajectory curve obtained by the simulation method can directly reflect the meshing law of the components.